Analysis of the Effect of ROE, DPR, Growth, on Price Book Value (PBV) at PT. Unilever 2020–2022 - Rizka Maya Shova; Sella Harvianna; Maria Yovita R.Pandin (International Journal of Economics and Management Research, 2024)
PBV (Price to Book Value) is the ratio of the stock market price to the book value per share. PBV shows how far a company is able to create company value relative to the amount of capital invested. The higher the PBV value, the more successful the company is in creating value for shareholders. This research aims to determine the effect of stock assessments on ROE, DPR, Growth on PBV in the 2020-2022 period. This research is research using quantitative methods. It is said to be a quantitative method because the data collected comes from the Indonesia Stock Exchange (BEI) in the form of financial reports. The results obtained after the analysis were carried out were that there was an influence between the ROE, DPR, Growth variables on the PBV variable in the PT Financial Report. Unilever 2020-2022.